Small molecule induces mitochondrial fusion for neuroprotection via targeting CK2 without affecting its conventional kinase activity - Ke-Wu Zeng; Jing-Kang Wang; Li-Chao Wang; Qiang Guo; Ting-Ting Liu; Fu-Jiang Wang; Na Feng; Xiao-Wen Zhang; Li-Xi Liao; Mei-Mei Zhao; Dan Liu; Yong Jiang; et al. (Signal Transduction and Targeted Therapy)
Abstract Mitochondrial fusion/fission dynamics plays a fundamental role in neuroprotection; however, there is still a severe lack of therapeutic targets for this biological process. Here, we found that the naturally derived small molecule echinacoside (ECH) significantly promotes mitochondrial fusion progression. ECH selectively binds to the previously uncharacterized casein kinase 2 (CK2) α′ subunit (CK2α′) as a direct cellular target, and genetic knockdown of CK2α′ abolishes ECH-mediated mitochondrial fusion. Mechanistically, ECH allosterically regulates CK2α′ conformation to recruit basic transcription factor 3 (BTF3) to form a binary protein complex. Then, the CK2α′/BTF3 complex facilitates β-catenin nuclear translocation to activate TCF/LEF transcription factors and stimulate transcription of the mitochondrial fusion gene Mfn2. Strikingly, in a mouse middle cerebral artery occlusion (MCAO) model, ECH administration was found to significantly improve cerebral injuries and behavioral deficits by enhancing Mfn2 expression in wild-type but not CK2α′+/− mice. Taken together, our findings reveal, for the first time, that CK2 is essential for promoting mitochondrial fusion in a Wnt/β-catenin-dependent manner and suggest that pharmacologically targeting CK2 is a promising therapeutic strategy for ischemic stroke.